UNODA Occasional Papers No. 27: Sessions of the Nuclear Discussion Forum, December 2015 - United Nations Office for Disarmament Affairs (United Nations, 2016)
The United Nations Office for Disarmament Affairs (UNODA) Occasional Papers is a series of ad hoc publications presenting, in edited form, papers or statements made at meetings, symposiums, seminars, workshops or lectures that deal with topical issues in the field of arms limitation, disarmament and international security. They are intended primarily for those concerned with these matters in Government, civil society and in the academic community. This publication contains the presentations made during the Nuclear Disarmament Forum (NDF) held in 2015. Founded in 2011 by the Permanent Mission of the Republic of Kazakhstan to the United Nations, the NDF has proven itself to be a very useful addition to the global debate on nuclear non-proliferation, disarmament and security. It serves a unique function as a venue for informal diplomacy and allows for an honest exchange of ideas on how the international community can work towards its shared goal of a world free of nuclear weapons.